2020
DOI: 10.1186/s12935-020-01362-0
|View full text |Cite
|
Sign up to set email alerts
|

Immune-related long non-coding RNA signature identified prognosis and immunotherapeutic efficiency in bladder cancer (BLCA)

Abstract: Background: As bladder cancer was recognized to be immunogenic, dozens of studies have focused on immune biology of BLCA, but little is known about its relationship with the long non-coding RNAs (lncRNAs). Methods: LASSO Cox regression model was used to establish immune-related lncRNAs signature (IRLS) in BLCA. The immune infiltration landscape of BLCA was conducted via ssGSEA and immunotherapy response was calculated through TIDE algorithm. Results: A total of 82 immune-related lncRNAs were screened out accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 62 publications
(60 reference statements)
6
57
0
Order By: Relevance
“…Chen et al demonstrated a 10-gene biomarker panel based on the consolidation of data derived from transcriptomics and proteomics to predict the occurrence of BLCA with diagnostic sensitivity of 79% and specificity of 79% in a multicenter cohort [ 63 ]. Recently, our group even constructed an immune-related lncRNA panel to predict the immunotherapeutic efficiency in BLCA [ 64 ]. Similarly, the EMT-LN signature established in the recent study showed a significantly different distribution in LN+ and LN- tumours in TCGA-BLCA training and testing cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al demonstrated a 10-gene biomarker panel based on the consolidation of data derived from transcriptomics and proteomics to predict the occurrence of BLCA with diagnostic sensitivity of 79% and specificity of 79% in a multicenter cohort [ 63 ]. Recently, our group even constructed an immune-related lncRNA panel to predict the immunotherapeutic efficiency in BLCA [ 64 ]. Similarly, the EMT-LN signature established in the recent study showed a significantly different distribution in LN+ and LN- tumours in TCGA-BLCA training and testing cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…More and more evidences has strongly supported that immune-related lncRNAs may be novel disease biomolecules for cancer clinic treatment and possess valuable prognostic signi cance for survival [38,39]. Several immune-related lncRNA signatures have been explored in some tumors, such as bladder cancer, breast cancer, and colon cancer [40][41][42]. Nevertheless, the latent role of immune-correlated lncRNAs risk score model as a helpful predictive indicator needs further validated in cancer immune checkpoint therapy, especially in BRCA.…”
Section: Discussionmentioning
confidence: 99%
“…More and more evidences has strongly supported that immune-related lncRNAs may be novel disease biomolecules for cancer clinic treatment and possess valuable prognostic signi cance for survival (42,43). Several immune-related lncRNA signatures have been explored in some tumors, such as bladder cancer, breast cancer, and colon cancer (44)(45)(46). Nevertheless, the latent role of immune-correlated lncRNAs risk score model as a helpful predictive indicator needs further validated in cancer immune checkpoint therapy, especially in PDAC.…”
Section: Discussionmentioning
confidence: 99%